Saying more than her name: Characterizing fatal police violence against Black women & girls in the US, 2000-2019 - Jé Judson; Kene Orakwue; Sirry Alang (Elsevier, 2024)
Background: Black women and girls (BWGs) face an elevated risk of being killed by police, yet few studies have focused on the proximal factors increasing their exposure to these deadly encounters. Objective: This paper elucidates the determinants and features of fatal police encounters with BWGs over a 20-year period. We examined (1) the initial cause of police contact, (2) how the encounter unfolded and escalated to a fatality, and (3) trends in factors salient to how each case transpired. Methods: Using the Fatal Encounters database, we identified 573 BWGs killed between 2000 and 2019. Using a qualitative descriptive approach, we leveraged case descriptions and triangulated with news articles, police reports, legal documents, and other texts about decedents to determine what happened in each case, why, and to what effect. Results: While many fatal police encounters were precipitated by alleged criminal activity, a significant number were due to minor violations, public health crises, and domestic violence. Moreover, most BWGs were not the target of the police activity that ultimately killed them, and their deaths came as collateral damage from the aggressive policing of others. Conclusion: As the US continues to grapple with the role of policing in community safety, this work complicates the understanding of how police operate and impact communities, raising questions about how to effectively address root causes beyond carceral and punitive frameworks.